Sistem Pengendalian Manajemen: Optimalisasi Pengendalian Internal Pada Penjualan Barang Dagangan - Joys Oktavia; Desfi Dwi; Hwihanus Hwihanus (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to evaluate the effectiveness of the internal control system for the sale of merchandise at Jazzy Souvenir Store. The approach used is a qualitative descriptive method with the application of data analysis techniques using triangulation. Data collection is carried out through observation, interviews, and documentation. The analysis results indicate that the internal control system for the sale of merchandise at Jazzy Souvenir Store is not yet optimal, as evidenced by the lack of adequate organizational structure and the existence of dual functions in the execution of tasks and responsibilities. Additionally, negligence in inventory recording by store employees leads to discrepancies between the physical inventory of merchandise and the recorded inventory in the system.